The Impact of Age on Sentencing in Child Murder Cases: An Analysis of the Implementation of Juvenile Justice Law in Indonesia - Hutapea, Frina Debora; Sharon, Grace (Justice Voice, 2025)
This study examines the role of age in the imposition of criminal charges against children involved in murder, focusing on the application of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law). The research highlights the perceived inequality of justice experienced by the victim’s family, particularly in cases where perpetrators under the age of 14 are sentenced to rehabilitation instead of imprisonment. The aim of this study is to analyze the extent to which Indonesian legal provisions consider age in sentencing child murderers, as well as how restorative justice is applied in such cases, and whether it addresses or exacerbates the sense of justice. This research employs a normative juridical method with qualitative analysis, supported by statutory, conceptual, case law, and comparative approaches. The findings reveal that while the SPPA Law offers special protection for children in conflict with the law, its application in cases of murder by young children presents a justice dilemma, particularly when the victim’s life is lost and the perpetrator does not receive proportionate criminal sanctions.